The impact of breastfeeding peer support for mothers aged under 25: a time series analysis - Scott, Sarah; Pritchard, Catherine; Szatkowski, Lisa (Wiley, 2016)
Breastfeeding is known to have positive health benefits for babies and mothers, yet the UK has one of the lowest breastfeeding initiation rates in Europe. Despite national guidance that recommends provision of breastfeeding peer support, there is conflicting evidence regarding its effectiveness, especially in high income countries, and a lack of evidence amongst young mothers. This study evaluates the effectiveness of a breastfeeding peer support service (BPSS) in one UK city in increasing breastfeeding initiation and duration in young mothers. Routinely-collected data were obtained on feeding method at birth, two and six weeks for all 5,790 women aged <25 registered with a local general practitioner and who gave birth from April 2009 to September 2013. Segmented regression was used to quantify the impact of the introduction of the BPSS in September 2012 on the prevalence of breastfeeding at birth, two and six weeks, accounting for underlying trends. Results showed that breastfeeding prevalence at birth and two weeks began to increase month-on-month after the introduction of the BPSS, where previously figures had been static; prevalence at birth increased by 0.55 percentage points per month (95%CI 0.10-1.00, p=0.018) and at two weeks by 0.50 percentage points (95%CI 0.15-0.86, p=0.007). There was no change from an underlying marginally increasing trend in prevalence at six weeks. In conclusion, our findings suggest that a one-to-one breastfeeding peer support service provided by paid peer supporters and targeted at young mothers in the antenatal and postnatal periods may be beneficial in increasing breastfeeding initiation and prevalence at two weeks.